Estimation of heritability and genetic correlation of egg production traits using animal model in commercial layer - CHANDAN, P; PRINCE, L L L; BHATTACHARYA, T K; RAJKUMAR, U; CHATTERJEE, R N (The Indian Journal of Animal Sciences, 2019)
Traditionally, heritability has been estimated by correlations of close kin. It is likely to be biased by determinants such as non genetic factors, inbreeding, selection and shared environment. Whereas, an animal model takes into account all relationships in a pedigree and is therefore expected to provide estimates of quantitative genetic parameters with higher precision. Therefore, the egg production data in the current study was analyzed using animal model to have more precise and accurate estimates of genetic parameters. The heritability of growth and egg weight traits was moderate to high. Whereas the heritability was lower for egg number and ASM traits. The body weights were positively correlated with egg weights and negatively correlated with egg numbers traits. The egg number produced at different age intervals was positively correlated. The genetic correlation of EP40 and EP52 with EP64 were 0.83 and 0.92, respectively. Therefore, the part period egg production of EP52 would give better selection response for egg production at 64 than EP40. Therefore, the selection of higher egg numbers can be done earlier at 52 weeks rather than waiting for EP64.